Internalised homophobia is differentially associated with sexual risk behaviour by race/ethnicity and HIV serostatus among substance-using men who have sex with men in the United States. (15th December 2014) - Mansergh, Gordon; Spikes, Pilgrim; Flores, Stephen A; Koblin, Beryl A; McKirnan, David; Hudson, Sharon M; Colfax, Grant N
Abstract : Objectives: There is a continuing need to identify factors associated with risk for HIV transmission among men who have sex with men (MSM), including a need for further research in the ongoing scientific debate about the association of internalised homophobia and sexual risk due partly to the lack of specificity in analysis. We assess the association of internalised homophobia by race/ethnicity within HIV serostatus for a large sample of substance-using MSM at high risk of HIV acquisition or transmission. Methods: Convenience sample of substance-using (non-injection) MSM reporting unprotected anal sex in the prior 6 months residing in Chicago, Los Angeles, New York and San Francisco. The analytic sample included HIV-negative and HIV-positive black (n=391), Latino (n=220), and white (n=458) MSM. Internalised homophobia was assessed using a published four-item scale focusing on negative self-perceptions and feelings of their own sexual behaviour with men, or for being gay or bisexual. Analyses tested associations of internalised homophobia with recent risk behaviour, stratified by laboratory-confirmed HIV serostatus within race/ethnicity, and controlling for other demographic variables. Results: In multivariate analysis, internalised homophobia was inversely associated (p<0.05) with recent unprotected anal sex among black MSM, and not significantly associated with sexual risk behaviour among white and Latino MSM. Conclusions: More research is needed to further identify nuanced differences in subpopulations of MSM, but these results suggest differentially targeted intervention messages for MSM by race/ethnicity.